(untitled) (Altre Modernità, 2023)
The Covid-19 pandemic has generated a number of studies on the use of metaphor to frame the disease and the trope has been presented as a prominent feature of Covid-19 discourse. The metaphor of war has been identified as the master metaphor for framing the health emergency, prompting reflections about its possible drawbacks and feasible alternative framings in order to generate a more constructive stance among the general public, politicians and administrators. Such studies largely refer to corpora drawn from heterogeneous sources, combining official statements with coverage in mainstream media, blogs and opinion pieces. The present study is based exclusively on a homogeneous single-genre corpus, namely the official Covid-19 announcements made by the former British Prime Minister Boris Johnson from the beginning of March 2020 to December of the same year. Using automated interrogation routines, frequency and keyword functions were examined to define the extent and expose underlying patterns of metaphor use in this genre. The quantitative data was also subjected to qualitative analysis from the perspective of Extended Conceptual Metaphor Theory, which led to insights into contextual constraints and cultural facets of metaphor use in this genre. The results obtained could be considered surprising. It emerged that Boris Johnson resorted to metaphor only sparingly in this genre. The results highlighted that, on the rare occasions when he did rely on this trope, his usage was very predictable and conventional. However, despite the low frequency and keyness of metaphor in his Covid-19 announcements, this rhetorical figure was seen to offer diverse resources and produce multiple effects, even when used so conservatively.